Reading Margery Kempe’s inner voices - Saunders, Corinne; Fernyhough, Charles (postmedieval: a journal of medieval cultural studies, 2017)
This article draws on research from the major collaborative research project Hearing the Voice, based at Durham University, to reconsider and foreground Margery Kempe’s inner voices, and hence, to return to an emphasis on inner, spiritual experience as shaping her Book. The richness of Margery’s multi-sensory experience, and the care with which it is depicted, is illuminated by and illuminates the experience of contemporary voice-hearers, offering a powerful alternative perspective to often reductive bio-medical understandings. Contemporary cognitive frameworks, particularly scientific accounts of inner speech, are in turn employed to open out Margery’s inner voices and to offer insights into the psychology of spiritual meditation.
EPrint Processing Status: Full text deposited in DRO